Důchodová reforma a rizika zabezpečení na penzi - Spurný, Jiří (Vysoké učení technické v Brně. Ústav soudního inženýrství, 2014)
Diplomová práce pojednává o penzijní reformě a penzijním systému v České republice. Vysvětluje základní pojmy v této oblasti a popisuje jejich fungování. Hlavní náplní práce je definice a ohodnocení rizik jednotlivých částí systému. Dílčím úkolem je rada pro využívání jednotlivých části v rámci systému.

The diploma thesis deals with the pension reform and the pension system in the Czech Republic. The paper explains fundamental terms in the field and explains their function. The main aim of the thesis is a definition and risk analysis of individual parts of the pension system. The secondary aim is guidance how to use each of the parts of the system.
Pension reform in the Czech Republic and its risks
Keywords: penzijní reforma; penze; pilíře penzijní reformy; první pilíř; druhý pilíř; třetí pilíř; spoření na penzi; pension reform; pension; pension reform pillars; firts pillar; second pillar; third pillar; pension saving